Apakah Hutan Hujan Tropis Dapat Meredam Dampak Pemanasan Global? (Studi Kasus Keseimbangan Energi dan Air di Sekitar TNLL.) - Sance Lipu (Biocelebes, 2009)
Global warming is a hot issue recently. Specially in climate and meteorology researcher. There is no doubt that global warming was effects almost all life around the world. Global warming can defined as the increase in the average temperature of the Earth's near-surface air and oceans caused by greenhouse gases mainly CO2. Two main factors caused global warming are natural effect and anthropogenic factors. The changes in global climate indicated by widely fluctuation of wet season and dry season, and Ozon (O3) reduce in pole area. These effects will follow by ice melt in artic and antartic. Study in Lore Lindu National Park around 2002 until 2005 indicated that tropical rain forest is a an ecosystem that very good function for absorb solar radiation, greenhouse gases and keeping sustainability of soil function as reservoir mineral and water. Forest conversion and illegal logging will increased solar radiation effect, decreased of CO2 and methane absorbed, decreased capacity of evapo-transpiration, and decreased water infiltration through the ground. Key words: tropical rain forest, Global warming effect.